Conceptual framework for leadership in public service - Haitov, P. O. (Aspekty publichnoho upravlinni͡a, 2016)
The article analyzes the conceptual foundations of leadership in the public service. The author comes from the fact that the concept of leadership is a theoretical construct that includes strategy, main directions, objectives and goals of improving public service personnel, to enhance the efficiency of state institutions due to indirect effects of leadership on organizational performance management. According to the author, the concept of leadership in the public service should be a system of coordinated actions which aim not only organizational improvement, but above all to optimize the role of the state, which has not only assist in the implementation of the interests of the population, but also actively participate the formation of civil society. The purpose of the formation and leadership development in the public service is to achieve a new quality vnutryorhanizatsiynoyi interaction that facilitates optimization of power structures as the subject of management and their interaction with the citizens as the object of control. Concept development based on scientific principles, consistency, complexity, individualization, availability. The functional HR service load state body in the direction of leadership. The main provisions defining the conceptual foundations of leadership in the public service, the author highlights: the educational component, regulated by different procedures to change learning within the application of modern methods of active influence on the personality of students to prepare for practice the last management activities; transformation of HR services of state bodies aimed at active inclusion in the formative activities to improve the quality of management interaction subject and object management.